Mental Nerve Neuropathy: A Rare Manifestation in Sickle Cell Disease - Alcafache, M (2018)
Mental nerve neuropathy is a peripheral sensory neuropathy, characterized by acute numbness of the chin area. It is a rare entity with diverse aetiology including, among others, local odontogenic causes and malignancy. In rare cases, it might be associated with sickle cell disease, due to the combined presence of hyperviscosity and the sinuous course of the mental nerve and artery through the mental foramen. The authors present the case of an adolescent girl with numb chin symptoms during a multifocal sickle cell crisis. The aim is to briefly review the causes of numb chin syndrome, emphasizing the differential diagnosis in sickle cell patients